Model Inovasi Pemerintah Daerah Bidang Pelayanan Perizinan dalam Mewujudkan Smart City (Studi Pendekatan Sistem Dinamik pada Pemerintah Kabupaten Sragen) - Eko Wismanu, Rendra; Nuh, Mohammad; Widodo, Nurjati; Aziz, Nana Abdul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
This study aims to see the innovation model of local government in an effort to provide public services online licensing field in Kabupaten Sragen, Central Java Province. Online-based licensing service implemented by the local government of Kabupaten Sragen is part of the government's efforts in realizing Smart City. The effort to realize Smart City in Kabupaten Sragen is the result of the synergy of all stakeholders, from the government, the public, the private sector and the international community. Therefore, this research tries to give an idea about ideal model of Smart City realization especially in the field of licensing service with dynamic system method approach. This methodology focuses on the modeling of local government innovations in viewing the behavior of problems and strategic issues of licensing services dynamically, so that later this model can serve as agrand design for the development of other areas in Indonesia that are heading towards the realization of Smart City.